Assessing the implementation of the 5s system in Syrian hospitals: A field study of private hospitals in latakia governorate - Hamdoush, Rasha; Zeitoun, Gheed; Sleman, Hala; Ramadan, Karam (International Journal of Social and Administrative Sciences, 2025)
This study aimed to diagnose the current state of 5S implementation in private hospitals in Latakia. The sample consisted of 116 participants drawn from four hospitals: Noor, Hikmah, Central, and Sayyeda Hospitals. The participants spanned diverse roles, including medical, administrative, and service staff. Data was collected through a questionnaire specifically designed for this study, with the aim of measuring the extent of implementing the 5S principles. The questionnaire was distributed randomly to staff in private hospitals in Latakia. Responses were recorded on a 5-point Likert scale (1 = Strongly disagree, 5 = Strongly agree). Data were analyzed using SPSS-25; Cronbach’s Alpha coefficients were calculated for each dimension to confirm reliability, including calculations of means and standard deviations. The collected data were encoded, processed, and analyzed using SPSS 25. Various statistical techniques were used to test the hypotheses. The most important results of hypothesis testing:1. Showed a significant, effective application of the "classification" principle within the 5S system. 2. The "sorting and organizing" principle was effectively implemented, indicating organized work environments that facilitate easy access to tools. 3. The "cleaning and shining" principle was strongly applied, reflecting high standards of cleanliness and quality. 4. The "setting standards" principle was actively applied, demonstrating ongoing efforts to establish uniform procedures.5. The hospitals demonstrated a commitment to continuous 5S principles, integrating them into organizational culture rather than temporary measures.